PENGARUH MOTIVASI KERJA, KOMUNIKASI ANTAR PRIBADI DAN KOMITMEN ORGANISASI TERHADAP KINERJA PEJABAT STRUKTURAL DAN DOSEN TETAP DI BEBERAPA PERGURUAN TINGGI SWASTA DI JAKARTA - Ismuhadjar, Ismuhadjar (Magister Manajemen, Fakultas Ekonomika dan Bisnis Undip, 2006)
The objective of this study is to search empirically the influences ofjob motivation, interpersonal communication, and organizational commitment towardjob-performance. Sample of the study consists of 90 respondents randomly selected from structural and academic staffs from 4 (four) private higher education institutions within The Coordination of Private Higher Educational Institutions, Region Ill (Koordinasi Perguruan Tinggi Swasta Wilayah Ill) Jakarta. Hypotheses of the study stated that :Â